Philosophy in Erection. Issue 2 (July 2016) - Malabou, Catherine
Abstract : Dialectics operates, Derrida writes, 'in raising or erecting what falls'. Yet the Hegelian system is problematized in the sense that, in the Genet column of Glas, what substitutes for the system is not a well-grounded philosophical alternative, but a sort of disseminal substitution itself, working within as much as against the system it resists. The confrontation staged by the text is not between homosexual transgression, on the one hand, and heterosexual normativity as the origin of the social bond, on the other, but instead a confrontation between two perspectives on the transcendental. The problem of Glas is that the two columns seem to 'come out the same' (in French 'revenir au même', amounting to the same) at the very moment when they seem to radically differ or diverge. Put differently, this problem is that of a contagion between the two sides. Why is there a risk of contagion and of similarity? What does this do to the transcendentality in question?